Psychological Well-Being Differences Between PNS Lecturers And Non-PNS Lecturers At UIN Raden Fatah Palembang - Listya Istiningtyas (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2020)
There are two permanent lecturers at UIN Raden Fatah Palembang, namely PNS (Civil Servant) and Non-PNS (Non-Civil Servant) lecturers, but for Non-PNS lecturers there are differences in treatment and legal uncertainty in that status. This study focuses on knowing the differences in psychological well-being between PNS and Non-PNS lecturers at UIN Raden Fatah Palembang. This research is a comparative quantitative study. From 25% of the population the number of research subjects is 125 people (81 PNS lecturers and 44 Non-PNS lecturers). The measuring tool uses for the dimensions of psychological well-being is a modified scale and adapted from Ryff and Keyes (1995). The data analysis method used was the Independent Sample t-test using SPSS 24.0. The result of hypothesis test shows a significance value that states Ha is accepted and H0 is rejected. In conclusion, there is a significant difference between the psychological well-being of PNS lecturers and non-PNS lecturers at UIN Raden Fatah. The mean variant of Non-PNS lecturers is also smaller, meaning that the psychological well-being of PNS lecturers is higher than Non-PNS lecturers.